C3, C5a and anti-acetylcholine receptor antibody as severity biomarkers in myasthenia gravis - Aguirre, Florencia (2020)
Background: Although the pathogenesis of myasthenia gravis (MG) is well known, prognostic markers are not yet available. We assessed the utility of anti-acetylcholine receptor (AChR) antibody (AChR-ab) titer and concentration of C3, C4, and C5a as potential severity biomarkers in MG. Methods: Levels of C3, C4, C5a, and AChR-ab were measured in 60 AChR-ab-positive patients with MG. Their relationship with clinical severity was analyzed using the activities of daily living (ADL) and MG composite (MGC) scales. Results: AChR-ab titer correlated with severity of MG according to ADL (p = 0.002) and MGC scales (p = 0.001). When patients were classified according to disease duration, a statistically significant correlation between AChR-ab titer and clinical severity was only found in the subgroup of patients with fewer than 5 years from symptoms onset. C5a levels showed a positive correlation with MG severity according to the ADL scale (p = 0.041; τb = 0.18), although C5a levels were not different from the control group. Discussion: AChR-ab titers and C5a levels could potentially be considered markers of severity in patients with MG.